2017
DOI: 10.1016/j.bonr.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Low health related quality of life associated with fractures in obese postmenopausal women in Santa Maria, Brazil

Abstract: Although health-related quality of life is well studied in subjects with obesity or fractures, there are few studies approaching both diseases together. The aim of this study was to evaluate the health-related quality of life (HRQL) in obese postmenopausal women with fractures. A cross-sectional study was carried out at Santa Maria, Brazil. Postmenopausal women aged 55 years or older were recruited from March 1st to August 31st, 2013. Women with cognitive impairment were excluded. The Short-Form Health Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…It will be important however to clearly assess these potential relationships in future longitudinal studies among women with HIV from this region. Finally, compared to the population of a Brazilian monocentric study of 1,057 older woman (mean age 67.1 years) using the SF-36 among women with and without fractures and obesity [ 30 ], both HIV-infected and uninfected women from our sample scored lower in both the physical and mental component scores compared to the control group (non-obese without fracture) from that study. This population also followed the pattern of "physical functioning" and "social functioning" being relatively high and "general health" and "energy fatigue" being relatively low compared to the other scores.…”
Section: Discussionmentioning
confidence: 97%
“…It will be important however to clearly assess these potential relationships in future longitudinal studies among women with HIV from this region. Finally, compared to the population of a Brazilian monocentric study of 1,057 older woman (mean age 67.1 years) using the SF-36 among women with and without fractures and obesity [ 30 ], both HIV-infected and uninfected women from our sample scored lower in both the physical and mental component scores compared to the control group (non-obese without fracture) from that study. This population also followed the pattern of "physical functioning" and "social functioning" being relatively high and "general health" and "energy fatigue" being relatively low compared to the other scores.…”
Section: Discussionmentioning
confidence: 97%
“…One article described the use of the FRAX tool in obese women and concluded that high body mass index could mask the risk of fractures, underestimating this outcome 13 .…”
Section: Chart 1 Description Of Articles Included In Integrative Revmentioning
confidence: 99%
“…8) Another study has also suggested that obese women with fractures had a significantly lower QOL than non-obese participants with fractures. 9) According to the Korea National Health and Nutrition Examination Survey, there was a negative association between obesity and HRQoL due to obesity-related diseases in both men and women. 10) Therefore, the relationship between obesity and HRQoL clearly deserves a close attention.…”
Section: Introductionmentioning
confidence: 99%
“…A study has also reported that obese individuals had a significantly lower health-related quality of life (HRQoL) than individuals that were within the normal weight range in the United States general population [ 8 ]. Another study has also suggested that obese women with fractures had a significantly lower QOL than non-obese participants with fractures [ 9 ]. According to the Korea National Health and Nutrition Examination Survey, there was a negative association between obesity and HRQoL due to obesity-related diseases in both men and women [ 10 ].…”
Section: Introductionmentioning
confidence: 99%